2022
DOI: 10.1186/s12887-022-03651-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal characteristics with child feeding indicators and nutritional status of children under-two years in Rural Ghana

Abstract: Background Optimal nutrition during the first two years of a child’s life is critical for the reduction of morbidity and mortality. In Ghana, majority of children miss out on optimal nutrition and only few (13%) of children receive a Minimum Acceptable Diet (MAD). Several studies have investigated the influence of community-level factors on infants and young children feeding (IYCF) practices. However, little is known about the influence of maternal factors on IYCF practices in rural settings. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…In this study, children whose mothers used family planning methods were approximately twice as likely to have diversified foods than their counterparts. This could be associated with such economically helpful factors as wider birth spaces, stable employment, better postnatal health, and providing women with more decision-making power, time and energy to prepare foods from diversified groups 73–76. Conversely, larger family size was typically associated with decreased childcare and LDD 77.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, children whose mothers used family planning methods were approximately twice as likely to have diversified foods than their counterparts. This could be associated with such economically helpful factors as wider birth spaces, stable employment, better postnatal health, and providing women with more decision-making power, time and energy to prepare foods from diversified groups 73–76. Conversely, larger family size was typically associated with decreased childcare and LDD 77.…”
Section: Discussionmentioning
confidence: 99%
“…This could be associated with such economically helpful factors as wider birth spaces, stable employment, better postnatal health, and providing women with more decisionmaking power, time and energy to prepare foods from diversified groups. [73][74][75][76] Conversely, larger family size was typically associated with decreased childcare and LDD. 77 However, only approximately 15% of the mothers used any form of family planning methods in the current study.…”
Section: Open Accessmentioning
confidence: 99%
“…Based on previous studies done in different settings, factors were identified to be significantly associated with minimum meal frequency and IYCF practices. These include: age of child [ 5 , 6 , 19 24 ], sex of the child [ 24 ], sex of household head [ 16 , 25 ], media exposure [ 6 , 26 ], maternal working status [ 16 ], maternal decision making power on household activities [ 6 ], timely initiation of breastfeeding [ 27 ], current breastfeeding status [ 27 ], parity [ 5 , 6 ], postnatal visit [ 6 , 20 , 23 , 24 ], household wealth index [ 20 , 22 , 23 , 28 ], maternal age [ 2 ], maternal education [ 2 , 19 , 21 , 29 ], place of delivery [ 30 ], number of antenatal care (ANC) visits [ 22 ], place of residence [ 19 , 23 ], and region [ 2 , 20 ] were found associated with minimum meal frequency.…”
Section: Introductionmentioning
confidence: 99%
“…6 Stunting can be detrimental to children under five as it causes low intelligence, decreased endurance, and inhibited growth and development. 7 This will result in an increased risk of infections and non-communicable diseases in adulthood, as well as reduced productivity and economy. Reducing stunting is the first goal of the 2025 global nutrition targets and a key indicator of the sustainable development goals.…”
Section: Introductionmentioning
confidence: 99%